Osteologia craniana de Micrastur semitorquatus Vieillot, 1817 (Falconiformes: Falconidae) - Da Silva, Andreza Gomes; De Ferreira, Guilherme José Bolzani; Donatelli, Reginaldo José [UNESP]; Guzzi, Anderson (My University, 2012)
Micrastur semitorquatus, popularly known as Collared Forest-Falcon is an inhabitant of the rainforests of the Neotropical Region. Studies on the cranial osteology are scarce in the literature. To increase the knowledge about the anatomy of this species its cranial osteology was described and compared with other species of birds of prey. Three specimens of M. semitorquatus were examined at the Bird Division of the osteological collection at the Smithsonian National Museum of Natural History (USNM), Washington, DC (USNM: 245788, USNM 013493 and USNM 289773). Although the relationship between the form of a structure and its function is not fully established, many of the adaptations of the skull of M. semitorquatus may be related to this lifestyle and behavior, such as narrowing of the interorbital width, the robustness of pila supranasalis coupled with the prokinesis of the skull, a process developed post-orbital, and palatine expansion. In addition, the cranial osteology of M. semitorquatus can provide useful characters for cladistic analysis, sustaining the hypothesis of phylogenetic relationships with other species of the same genus or the same family.
Cranial osteology of Micrastur semitorquatus Vieillot, 1817 (Falconiformes: Falconidae)
Keywords: Birds; Falconidae; Micrastur semitorquatus; Osteology; Skull; Aves; Falconiformes; Pila; Raptores